Experimental Study on Corrosion of Anchored Rock Mass for Half-Through Intermittent Joints - Wantao Ding; Mingjiang Li; Mingbin Wang; Rui Chen; Yang Wang; Lei Chen (Advances in Civil Engineering)
Make crackled mortar test block to simulate jointed rock mass reinforced by anchor bars. Computational model of corrosion penetration at different load times can be obtained by corrosion acceleration through electrochemistry. Through observation of anchor bar after corrosion, it is found that primary corrosion is mainly pitting; however, with the development of corrosion, corrosion moves along etch pit to the upper and lower surfaces so as to form partial corrosion. Meanwhile, computational formula of pitting ratio is put forward on the basis of mass loss rate. It is found that, through the pulling out experiment of anchor bar corrosion, corrosion has remarkable influence on anchoring performance of anchor bar; meanwhile, different pitting ratios have different influences on trends of ultimate bond strength, for example, when pitting ratio is bigger (between 9% and 30%), the biggest decreasing rate of bond strength is obviously lower than that under lower pitting ratio (from 1.5% to 5%). According to linear fitting of experimental data, the relationship curve of K, ultimate bond strength ratio, and pitting ratio can be obtained so as to provide basis for judgement of anchoring performance loss in practical engineering.